The Effect of Blood Contamination on the Compressive Strength of Calcium-Enriched Mixture - Adl, Alireza (J Dent (Shiraz), 2015)
STATEMENT OF THE PROBLEM: In clinical situations, Calcium-Enriched Mixture (CEM) comes into direct contact or even mixes with blood during or after placement. PURPOSE: The aim of this study was to evaluate the effect of blood contamination on the compressive strength of CEM. MATERIALS AND METHOD: Three experimental groups were included in this study. In the first group, CEM was mixed with distilled water and was exposed to normal saline (control group). In the second group, CEM cement was mixed with distilled water and then was exposed to blood. In the third group, CEM was mixed with and exposed to blood. Nine custom-made two-part split Plexiglas molds with five holes were used to form CEM samples for compressive strength testing (15 samples in each group). After 7 days of incubation, compressive bond strength testing was performed using a universal testing machine. Data were statistically analyzed using the Mann–Whitney U test with a significance level of p< 0.05. RESULTS: Nine samples from group 3 were fractured during removal from the molds; the other six blocks had some cracks on their surfaces. Therefore, a compressive strength measurement was not obtainable for this group. No statistically significant difference was found between groups 1 and 2 (p> 0.05). CONCLUSION: It can be concluded that exposure to blood does not adversely affect the compressive strength of CEM, but incorporation of blood makes the cement very brittle.